Factors effecting fixed-line telecom services customer retention: A study of Pakistan - Rind, M. Malook; Alzabi, Tami; Ujan, Imran Anwar; Shah, Asadullah (Islamic Countries Society of Statistical Sciences. (ISOSS), 2016)
The use of fixed line telecom services in Pakistan is declining gradually since past few years. The purpose of this research is to integrate model that helps to evaluate the main determinants of fixed line telecom services' post purchase intention. This research proposes a comprehensive integrated framework that may help to measure the relationship among stability, content quality, responsiveness, staff attitude, functional value, perceived customer value, monetary value, perceived service quality, customer satisfaction and their impact on post-purchase intention of telecom services. Baaed on the proposed framework build through a thorough literature review, authors intend to adopt quantitative, clustered sampling approach for data collection. A structured Equation Modelling (SEM) approach will be adopted to test and validate the acquired data. Finding of this research will help operate to make proactive, feasible decisions towards best utilization of their resources in maximizing profit, retaining customer base and achieving organization goals.